Spin correlated-plasmons at room temperature driven by electronic correlations in lead-free 2D hybrid organic-inorganic perovskites - Muhammad Avicenna Naradipa (2022)
Hybrid organic-inorganic perovskites (HOIPs) have emerged to the forefront of optoelectronic material advancements for the past few years. However, our understanding on electronic structure and correlations are still lacking. Herewith, by simultaneously analyzing complex dielectric function, loss functions, and reflectivity directly obtained from spectroscopic ellipsometry and supported with theoretical calculations, we report new spin correlated-plasmons with low loss in (MA)2CuCl4. Photoluminescence and time-resolved photoluminescence measurements show a broadband emission band originating from the self-trapped emission excitons. Through X-ray absorption spectroscopy and resonant photoemission spectroscopy measurements at the C K-edge, a resonance enhancement peak is observed and unravels a charge transfer event due to the opening of an extra autoionization channel. Our result shows the importance of coupling between spin correlated-plasmons and electron-hole pairs together with spin-dependent exchange interaction in determining electronic structure and optical properties of HOIPS.